Case Report: Tackling Complement Hyperactivation With Eculizumab in Atypical Hemolytic Uremic Syndrome Triggered by COVID-19 - Leone, Valentina Fanny; Imeraj, Amantia; Gastoldi, Sara; Mele, Caterina; Liguori, Lucia; Condemi, Carmelita; Ruggenenti, Piero; Remuzzi, Giuseppe; Carrara, Camillo (Frontiers in Pharmacology, 2022)
Hemolytic Uremic Syndrome (HUS) is a rare life-threatening disease of unrestrained complement system dysregulation, microangiopathic hemolytic anemia, thrombocytopenia and acute renal failure in genetically predisposed individuals. In this report we describe two cases of SARS-CoV-2 associated HUS treated with eculizumab, a C5-blocking monoclonal antibody reported to be remarkably effective in the treatment of HUS. Detailed biochemical and genetic complement system analysis is reported and the prompt clinical response after C5 pharmacological blockade is documented. Our report pro-vides the rationale and supports the use of terminal complement pathway inhibition for the treatment of SARS-CoV-2-associated HUS.